2019
DOI: 10.3390/cells8060525
|View full text |Cite
|
Sign up to set email alerts
|

Improved Oxygen Supply to Multicellular Spheroids Using A Gas-permeable Plate and Embedded Hydrogel Beads

Abstract: Culture systems for three-dimensional tissues, such as multicellular spheroids, are indispensable for high-throughput screening of primary or patient-derived xenograft (PDX)-expanded cancer tissues. Oxygen supply to the center of such spheroids is particularly critical for maintaining cellular functions as well as avoiding the development of a necrotic core. In this study, we evaluated two methods to enhance oxygen supply: (1) using a culture plate with a gas-permeable polydimethylsiloxane (PDMS) membrane on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Inclusion of chitosan microgels increases interstitial spacing in the densely packed cell aggregates allowing more efficient transport of oxygen into the spheroid core via a permeation/percolation mechanism. A recent study [ 35 ] with human hepatoma cell (HepG2) spheroids incorporating alginate beads showed a similar result, namely that inclusion of microbeads helped to reduce hypoxia responses in spheroids, especially when paired with a gas‐permeable culture plate system. To further understand spheroid responses to chitosan‐PFC microgels, we measured total ds‐DNA in spheroids (directly proportional to the number of live cells), employing the same design and 4‐day cell culture as the hypoxyprobe experiments (Figure 4C).…”
Section: Resultsmentioning
confidence: 78%
“…Inclusion of chitosan microgels increases interstitial spacing in the densely packed cell aggregates allowing more efficient transport of oxygen into the spheroid core via a permeation/percolation mechanism. A recent study [ 35 ] with human hepatoma cell (HepG2) spheroids incorporating alginate beads showed a similar result, namely that inclusion of microbeads helped to reduce hypoxia responses in spheroids, especially when paired with a gas‐permeable culture plate system. To further understand spheroid responses to chitosan‐PFC microgels, we measured total ds‐DNA in spheroids (directly proportional to the number of live cells), employing the same design and 4‐day cell culture as the hypoxyprobe experiments (Figure 4C).…”
Section: Resultsmentioning
confidence: 78%
“…The selection of PDMS as the eggshell material is based on its proven property of being gas permeable albeit dependent on thickness. 4,30,39,41,44,51 This mimics the porosity of the eggshell which assists in the passage of diffusible substances but yet acts as a barrier to infection. [52][53][54] Moreover, untreated PDMS 40,44 and the surface of eggshell membranes 55,56 possess a hydrophobic surface thus conferring PDMS as a suitable material.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37] PDMS possesses favorable unique properties as it is permeable to gases, chemically inert, thermally stable, rigid, and optically clear. [38][39][40][41] Lai and Liu 32 and Huang et al 30 have fabricated cubic eggshells made of PDMS with an internal egg-shaped feature in the former model but not in the latter. Huang et al 31 further developed the cubic eggshell to have the ability to direct blood vessel formation.…”
Section: Glass Bowl Glass Bowl With Clear Lid Angiogenesis and Vasculmentioning
confidence: 99%
“…Necrosis usually develops in spheroids of larger diameters, e.g., 400 to 600 µm, and reduces cell viability and proliferation 16 . To overcome these limitations, efforts have been made to artificially supply oxygen via fiber injection 17 - 20 . Moreover, spheroids scatter light and feature inhomogeneous dye diffusion 21 , rendering imaging very challenging.…”
Section: Introductionmentioning
confidence: 99%